M. G. Vassanji: An Interview - Rhodes, Shane (Studies in Canadian Literature, 1997)
Moyez Vassanji speaks to Shane Rhodes of his personal history of movings, the radical diversity in his life that has resulting from them, and how they affect his writing. Vassanji also notes his visits to India and that fact that the country demands a response from him as a writer. In discussing The Gunny Sack and his novels No New Land and The Book of Secrets, Vassanji also touches on the importance in his work of storyteller characters, deals with history and issues of colonialism, and comments the ways in which religious objects become mysterious, as well as the relationship between sex and mystery in his writing.